Polymerase-tautomeric model for the mechanism of formation of targeted delayed substitution mutations under the synthesis of DNA containing cis-syn cyclobutane thymine dimers - Grebneva, H. A. (Reports of the National Academy of Sciences of Ukraine, 2016)
For the first time, a mechanism of targeted delayed base substitution mutations caused by cissyn cyclobutane thymine dimers is proposed. Delayed mutations are mutations that may appear in a few cycles of replication after the exposure to a mutagen. Targeted delayed mutations appear opposite to DNA damages that are able to stop the synthesis of DNA. Structural analysis of the insertion of the bases showed that adenine can be incorporated opposite to the rare tautomeric form of thymine T∗ 3. But any other canonical base may be inserted so that hydrogen bonds are formed between them. If, in the synthesis of DNA containing the cis-syn cyclobutane dimer TT∗ 3, DNA polymerases with relatively high fidelity of synthesis are involved, mutations not appear. However, if the further DNA synthesis will involve DNA polymerases having a low fidelity of synthesis, there may be base substitution mutations. Moreover, they may be formed through many cycles of replication after the damage of DNA. Consequently, these are the delayed mutations. Thus, the polymerase-tautomeric model of ultraviolet mutagenesis is able to explain not only the nature and mechanisms of formation of hot and cold spots under the ultraviolet mutagenesis, targeted and untargeted substitution mutations, targeted deletions and targeted insertions, targeted complex mutations, but also targeted delayed substitution mutations. The nature of bystander effects and the genomic instability can be explained in the framework of the polymerase-tautomeric model as well.